Anti‐glycoprotein autoantibodies are related to bleeding severity in children with newly diagnosed ITP and very low platelet counts. Issue 2 (15th November 2022) - Dong, Shuyue; Gu, Hao; Zhang, Jialu; Fu, Lingling; Xie, Xingjuan; Ma, Jingyao; Ma, Jie; Chen, Zhenping; Wu, Runhui
Abstract: Background and objective: Immune thrombocytopenia (ITP) is an autoimmune‐mediated hemorrhagic disease. Anti‐glycoprotein autoantibodies play a key role in the pathophysiology of ITP, but the relationship between platelet‐specific antibodies and bleeding severity is unclear. This study aimed to analyze the relationship between anti‐glycoprotein autoantibodies and bleeding severity in children with newly diagnosed ITP and platelet count less than 10 × 10 9 /L. Method: This was a single‐center prospective observational study that analyzed children with newly diagnosed ITP and platelet count less than 10 × 10 9 /L between June 2018 and September 2021 at our hospital. The children were classified into the mild and severe groups based on the bleeding scores. The type and titer of anti‐glycoprotein autoantibodies were detected using an enzyme‐linked immunosorbent assay (ELISA) kit (PAKAUTO). We analyzed the relationship between bleeding severity and anti‐glycoprotein autoantibodies. Results: A total of 86 cases were enrolled, including 42 in the mild group and 44 in the severe group. Patients with anti‐GPIIb/IIIa or anti‐GPIb/IX antibodies suffered more severe bleeding than patients without them ( χ 2 = 7.303, p = .007; χ 2 = 3.875, p = .049), but there was no significant difference between patients with or without anti‐GPIa/IIa antibodies ( χ 2 = 0.745, p = .388). When antibodies were analyzed together, patients with three antibodies suffered more severe bleeding than those without three antibodies ( χ 2 = 5.053, p = .025). Patients with higher antibody titer in the eluent, but not in the plasma, suffered more severe bleeding in all three antibodies ( Z = −2.389, p = .017; Z = −2.108, p = .035; Z = −2.557, p = .011). Conclusion: Anti‐glycoprotein autoantibodies led to more severe bleeding in children under 18 years of age without drug treatment with newly diagnosed ITP and platelet count less than 10 × 10 9 /L.